2017
DOI: 10.1016/j.neuropharm.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The great divide: Separation between in vitro and in vivo effects of PSNCBAM-based CB 1 receptor allosteric modulators

Abstract: While allosteric modulators of the cannabinoid type-1 receptor (CB1) continue to be developed and characterized, the gap between the in vitro and in vivo data is widening, raising questions regarding translatability of their effects and biological relevance. Among the CB1 allosteric modulators, PSNCBAM-1 has received little attention regarding its effects in vivo. Recently, pregnenolone was reported to act as an allosteric modulator of CB1, blocking THC’s effects in vitro and in vivo, highlighting the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…In the same study, the compound was ineffective at attenuating the reduced locomotion, catalepsy, and hypothermia induced by CB 1 agonist Δ 9 -THC. Similar to Org27569, PSNCBAM-1 exhibited a modest but statistically significant reduction in the antinociceptive effects induced by the CB 1 agonist Δ 9 -THC [54]. The above results again revealed the functional selectivity of a CB 1 NAM.…”
Section: Therapeutic Relevance Of Cb 1 Allosteric Modulatorsmentioning
confidence: 58%
See 3 more Smart Citations
“…In the same study, the compound was ineffective at attenuating the reduced locomotion, catalepsy, and hypothermia induced by CB 1 agonist Δ 9 -THC. Similar to Org27569, PSNCBAM-1 exhibited a modest but statistically significant reduction in the antinociceptive effects induced by the CB 1 agonist Δ 9 -THC [54]. The above results again revealed the functional selectivity of a CB 1 NAM.…”
Section: Therapeutic Relevance Of Cb 1 Allosteric Modulatorsmentioning
confidence: 58%
“…The initial profile of this compound revealed that PSNCBAM-1 dose-dependently increased the binding of the CB 1 agonist [ 3 [53]. It also inhibited Δ 9 -THC-induced [ 35 S]-GTPγS binding [54]. In yeast reporter assays using the CB 1 receptor, PSNCBAM-1 blocked the agonistic effects of several CB 1 orthosteric agonists, including CP55,940, WIN55,212-2, AEA and 2-AG.…”
Section: Representative Cb 1 Allosteric Modulators and Their Allostermentioning
confidence: 99%
See 2 more Smart Citations
“…It further decreased food intake in normal and obese rodents without any adverse side effects [ 424 ]. However, many allosteric ligands so far being described and tested in vitro have not yet shown a sustained effect on CB1 signaling in vivo [ 425 ]. Thus, research still has to put a lot of effort into the successful establishment of allosteric CB1 ligands as potential future pharmacological tools in the clinics.…”
Section: Therapeutic Targeting Of the Ecs In Body Weight Regulatiomentioning
confidence: 99%